ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN TERHADAP PENGGUNA JASA TRANSPORTASI (studi kasus pada pengguna bus Trans Jogja di Kota Yogyakarta) - Ibnu Zakaria, Shandy; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2013)
This research was based on the level of consumer satisfaction, with the absence of similar competitors why the level of consumer satisfaction can’t reach the standardized level. This phenomenom is based on the variables quality of service, price perception, and brand image. The purpose on this study was to analyze the influence of quality service, price perception and brand image on consumer satisfaction of Trans Jogja Bus in Yogyakarta city. And this study also aims to analyze the most dominant factors influence on consumer satisfaction of TransJogja Bus in Yogyakarta city.The sample in this study is 100 respondents of user Trans Jogja bus. Questionnaire instrument is used as data collectors, and the techniques used are non-probability sampling techniques with the approach of accidental sampling (sampling based on chance). Validity and reliability testing that qualify as instrument. Multiple linear regression analysis is used to determine the effect of variable quality service, price perception and brand image on the consumer satisfaction. The quality of service variable has the most impact on consumer satisfaction, followed by price perception variable. While the brand image variable has lowest influence compared to other variables. Hypotesis testing using t-test showed that the three independent variables studied have influence on the consumer satisfaction. Then through the F test can be seen that these three variables simultaneously influencing consumer satisfaction.